2019
DOI: 10.1371/journal.ppat.1007609
|View full text |Cite
|
Sign up to set email alerts
|

Human IFIT proteins inhibit lytic replication of KSHV: A new feed-forward loop in the innate immune system

Abstract: Kaposi’s sarcoma-associated herpesvirus (KSHV) is causally associated with Kaposi’s sarcoma, primary effusion lymphoma (PEL) and multicentric Castleman’s disease. The IFIT family of proteins inhibits replication of some viruses, but their effects on KSHV lytic replication was unknown. Here we show that KSHV lytic replication induces IFIT expression in epithelial cells. Depletion of IFIT1, IFIT2 and IFIT3 (IFITs) increased infectious KSHV virion production 25-32-fold compared to that in control cells. KSHV lyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 65 publications
4
43
0
Order By: Relevance
“…4C and D). As a control, we tested IFIT1 binding to the U6 snRNA (RNU6), which has a gamma-monomethyl 5= cap, and we found, similarly to results reported previously by others (44), that IFIT1 did not bind this RNA. We next tested if CMTR1-regulated ISGs contained RNA elements that could dictate their sensitivity to translational repression by IFIT1.…”
Section: Resultssupporting
confidence: 75%
“…4C and D). As a control, we tested IFIT1 binding to the U6 snRNA (RNU6), which has a gamma-monomethyl 5= cap, and we found, similarly to results reported previously by others (44), that IFIT1 did not bind this RNA. We next tested if CMTR1-regulated ISGs contained RNA elements that could dictate their sensitivity to translational repression by IFIT1.…”
Section: Resultssupporting
confidence: 75%
“…However, we found that IFIT1 bound to both the CMTR1-regulated and -nonregulated transcripts following CMTR1 depletion ( Figure 4C-D ). As a control, we tested IFIT1 binding to the U6 snRNA ( RNU6 ), which has a gamma-monomethyl 5’ cap, and we found, similar to others, that IFIT1 did not bind this RNA (44). We next tested if CMTR1-regulated ISGs contained RNA elements that could dictate their sensitivity to translational repression by IFIT1.…”
Section: Resultssupporting
confidence: 60%
“…These proteins upregulate IFNβ and 2′,5′-oligoadenylate synthetase (OAS) proteins to promote the degradation of viral RNA. Loss of IFIT1, IFIT2, and IFIT3 leads to broad increases in lytic gene expression and subsequent virion production, implicating them in control of KSHV latency [ 45 ]. Interferon stimulation also changes cellular patterns of posttranslational modifications, particularly through the induction of interferon-stimulated gene 15 (ISG15) conjugation.…”
Section: Mechanisms Regulating the Maintenance Of Kshv Latencymentioning
confidence: 99%